Draft Annual Plan 1987-88 Volume : I An Overview Government of Assam - Planning Commission (Planning Commission, 1987)
The economy of Assam which had to pass through many stresses and, strains during the past ten years, appears to have now wall—set on the path of development. Due to various constraints, the autonomy of the State during the Sixth Plan period presented a mixed picture. However, with the successful start of the State’s Seventh Five Year Plan coupled with major initiatives towards boosting economic growth gearing up of poverty alleviation programmes, revitalising industrial and infrastructural sectors etc., a distinct improvement in the economy of the State is expected within the current Plan period. A brief Assessment of the economy of the State over the recent years is presented in the following paragraphs on the basis of available data.
Government of Assam, Planning and Development Department